It's okay to be different - Parr, Todd. (New York : Little, Brown, 2009)
Illustrations and brief text describe all kinds of differences that are "okay," such as being a different color, needing some help, being adopted, and having a different nose.
"Megan Tingley Books."
Book Links (A.L.A.)
Five Owls
School Library Journal
1.3
K-3.
Keywords: Individuality -- Juvenile fiction; Self-esteem -- Juvenile fiction; Individuality -- Fiction; Self-esteem -- Fiction; Individuality -- Fiction; Self-esteem -- Fiction